Rogozhin and Christ: an Attempt of Interpretation - Valentina S. Sergeeva (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
This article attempts to interpret one of the final episodes of F.M. Dostoevsky’s Novel The Idiot as a parallel to an event of Evangelic story, namely the co-crucifixion of Christ and the Good Thief. The possibility of such interpretation, in our opinion, is allowed by a certain correlation made by the author between the main character of the novel and Christ, and also by clear allusions to the Biblical scene of Crucifixion that can be traced in details describing the last meeting of Myshkin and Rogozhin (what’s more, these details, highlighted by Dostoevsky, refer also to the visualization of Crucifixion in iconography). Successfulness or unsuccessfulness of “prince Christ” therefore is perceived in the light of the effect made on Rogozhin by Myshkin’s last deed in the world of men. If the Good Thief should do an effort of repentance, Christ, on the other hand, accepts him with love and compassion despite all his past crimes – and Myshkin does the same, supposedly, giving Rogozhin a chance of purification and entering the new life.